2015
DOI: 10.1080/09168451.2014.951025
|View full text |Cite
|
Sign up to set email alerts
|

Fish protein intake induces fast-muscle hypertrophy and reduces liver lipids and serum glucose levels in rats

Abstract: (2015) Fish protein intake induces fast-muscle hypertrophy and reduces liver lipids and serum glucose levels in rats, Bioscience, Biotechnology, and Biochemistry, 79:1, 109-116,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 20 publications
5
38
2
Order By: Relevance
“…Dietary supplementation with conjugated linoleic acid or EPA/DHA increased body VO2 consumption, VCO2 production, and energy expenditure, with fish oil (EPA/DHA) being the most potent. Fish protein was proven to induce fast-muscle hypertrophy, and the enhancement of basal energy expenditure by muscle hypertrophy; the increase in muscle glucose uptake reduces liver lipids and serum glucose levels[39]. Recently, Zhao et al[40] demonstrated that peptides from the muscle of the Spanish mackerel have strong antioxidant activity, which correlated with our biochemical studies with CabyMar.…”
supporting
confidence: 70%
“…Dietary supplementation with conjugated linoleic acid or EPA/DHA increased body VO2 consumption, VCO2 production, and energy expenditure, with fish oil (EPA/DHA) being the most potent. Fish protein was proven to induce fast-muscle hypertrophy, and the enhancement of basal energy expenditure by muscle hypertrophy; the increase in muscle glucose uptake reduces liver lipids and serum glucose levels[39]. Recently, Zhao et al[40] demonstrated that peptides from the muscle of the Spanish mackerel have strong antioxidant activity, which correlated with our biochemical studies with CabyMar.…”
supporting
confidence: 70%
“…In rats, fish proteins have been shown to influence blood lipid concentrations [54,55]. Furthermore, Kawabata et al [56] reported that the consumption of fish proteins resulted in less epididymal adipose tissue and lower levels of plasma triglycerides in rats compared with the consumption of casein. In the same study, the authors found that fish protein was able to increase skeletal muscle weight, especially the fast-type muscle and fast-twitch fibers [56].…”
Section: Fish Proteins Function On Muscle Massmentioning
confidence: 99%
“…For example, the basal energy expenditure and insulin sensitivity were also associated with hepatic TAG accumulation (Kim and others ; Voshol and others ). Previous research reported that cod protein reduced hepatic TAG content through the enhancement of basal energy expenditure by induced the muscle hypertrophy and improved the insulin resistance and sensitivity in rats (Kawabata and others ). The basal energy expenditure and insulin sensitivity are necessary in next experiment in order to elucidate the mechanism of the of hepatic TAG accumulation.…”
Section: Resultsmentioning
confidence: 93%